BLENDED LEARNING STRATEGIES TO ENHANCE ACADEMIC WRITING SKILLS IN UNDERGRADUATE STUDENTS - SHAHIDATUL MASLINA BINTI MAT SOOD; NUR HAFEZAH HUSSEIN; NOOR SYAMIMIE MOHD NAWI; SYAKIRAH SHAFIEN; LENA RAMAMURTHY (MEDIA DIDAKTIKA, 2025)
Blended learning in Malaysia has become a popular educational approach as it integrates online and face-to-face learning to provide students with a more flexible and engaging experience. Many higher education institutions have adopted this approach to meet the needs of digitally savvy students while maintaining quality education. Using the UBI20402 Academic Reading and Writing course as a case study, the paper evaluates the integration of digital tools, multimodal resources, and structured teaching methodologies to achieve CEFR B2-level learning outcomes. A mixed-methods methodology was employed, comprising the analysis of student performance metrics, surveys to capture student feedback, and instructor observations. The results highlighted that blended learning significantly enhanced students' understanding of academic writing structures and processes. These include students who found the integration of digital tools and multimodal resources highly engaging and helpful for understanding complex academic texts, whilst instructor observations revealed that structured teaching methodologies increased classroom participation, collaboration, and students' critical thinking and analytical skills when combined with digital tools. In conclusion, blended learning strategies offer a solid foundation for teaching academic writing while effectively meeting the needs of a wide range of students. Future research could explore mobile-friendly platforms and examine the long-term impact of blended learning on students’ academic achievement.